Inhibition of UDP-glucuronosyltransferases (UGTs) by phthalate monoesters. (April 2018) - Du, Zuo; Cao, Yun-Feng; Li, Sai-Nan; Hu, Cui-Min; Fu, Zhi-Wei; Huang, Chun-Ting; Sun, Xiao-Yu; Liu, Yong-Zhe; Yang, Kun; Fang, Zhong-Ze
Abstract: Phthalate monoesters are important metabolites of phthalate esters (PAEs) which have been extensively utilized in industry. This study aims to investigate the inhibition of phthalate monoesters on the activity of various isoforms of UDP-glucuronosyltransferases (UGTs), trying to elucidate the toxicity mechanism of environmental endocrine disruptors from the new perspectives. In vitro recombinant UGTs-catalyzed glucuronidation of 4-methylumbelliferone (4-MU) was employed to evaluate 8 kinds of phthalate monoesters on 11 sorts of main human UGT isoforms. 100 μM phthalate monoesters exhibited negligible inhibition towards the activity of UGT1A1, UGT1A3, UGT1A6, UGT1A8, UGT1A10, UGT2B4, UGT2B7, UGT2B15 and UGT2B17. The activity of UGT1A7 was strongly inhibited by monoethylhexyl phthalate (MEHP), but slightly inhibited by all the other phthalate monoesters. UGT1A9 was broadly inhibited by monobenzyl phthalate (MBZP), monocyclohexyl phthalate (MCHP), MEHP, monohexyl phthalate (MHP) and monooctyl phthalate (MOP), respectively. MEHP exhibited competitive inhibition towards UGT1A7, and MBZP, MCHP, MEHP, MHP and MOP showed competitive inhibition towards UGT1A9. The inhibition kinetic parameters (Ki ) were calculated to be 11.25 μM for MEHP-UGT1A7, and 2.13, 0.09, 1.17, 7.47, 0.16 μM for MBZP-UGT1A9, MCHP-UGT1A9, MEHP-UGT1A9, MHP-UGT1A9, MOP-UGT1A9, respectively. Molecular docking indicated that both hydrogen bonds formation and hydrophobic interactions significantly contributed to the interaction between phthalate monoesters and UGT isoforms. All these information will be beneficial for understanding the adverse effects of PAEs. Graphical abstract: Image 1 Highlights: Phthalate monoesters showed broad inhibition on UGT1A9. Threshold values for inducing in vivo inhibition of UGTs were calculated. Both hydrogen bonds and hydrophobic interaction contributed to the inhibition of UGT1A9 by phthalate monoestersi.